Journeying with Communities: A Community Engagement and Organizing Handbook for University Extension Workers - Abenir, Mark Anthony Dayot (Archīum Ateneo, 2021)
This handbook highlights the public and social mission of higher educational institutions (HEI) through Community Engagement; a term that brings forth the important use of Participatory Action Research (PAR) and Community Organizing for Community Development (COCD). The unique contribution of this handbook is that it specifically situates HEI Community Engagement within the unique historical context of the Philippines; thus adding a Philippine voice in the literature of Community-Engaged Scholarship (CEnS). It also provides activity exercises and case studies where readers can situate themselves and apply the theories; concepts; and tools they have learned so they can enhance the Community Engagement programs and projects of their respective colleges and universities with their partner communities.